Transposable elements and G-quadruplexes - Kejnovsky, Eduard; Tokan, Viktor; Lexa, Matej (Chromosome research, 2015)
A significant part of eukaryotic genomes is formed by transposable elements (TEs) containing not only genes but also regulatory sequences. Some of the regulatory sequences located within TEs can form secondary structures like hairpins or three-stranded (triplex DNA) and four-stranded (quadruplex DNA) conformations. This review focuses on recent evidence showing that G-quadruplex-forming sequences in particular are often present in specific parts of TEs in plants and humans. We discuss the potential role of these structures in the TE life cycle as well as the impact of G-quadruplexes on replication, transcription, translation, chromatin status, and recombination. The aim of this review is to emphasize that TEs may serve as vehicles for the genomic spread of G-quadruplexes. These non-canonical DNA structures and their conformational switches may constitute another regulatory system that, together with small and long non-coding RNA molecules and proteins, contribute to the complex cellular network resulting in the large diversity of eukaryotes.
Keywords: transcription; genomika; G-quadruplexes; Retroelements; replikace DNA; transpozibilní elementy DNA; DNA Replication; recombination; G-Quadruplexes; vazba proteinů; transposable elements; Genomics; Humans; LTR retrotransposons; retroelementy; Repetitive Sequences, Nucleic Acid; Gene Expression Regulation; RNA; regulační oblasti nukleových kyselin; DNA vazebné proteiny; regulace genové exprese; DNA-Binding Proteins; repetitivní sekvence nukleových kyselin; Open Reading Frames; Plants; G-kvadruplexy; DNA Transposable Elements; otevřené čtecí rámce; replication; Regulatory Sequences, Nucleic Acid; lidé; rostliny; DNA and RNA quadruplexes; Protein Binding